SMAD4 Protein Expression Is Downregulated in Ileal Epithelial Cells from Patients with Crohn’s Disease with Significant Inverse Correlation to Disease Activity - Pia Klausen; John Gásdal Karstensen; Mehmet Coskun; Adrian Săftoiu; Peter Vilmann; Jack Bernard Cowland; Lene Buhl Riis (Gastroenterology Research and Practice)
Background. Small mothers against decapentaplegic (SMAD)4 and SMAD7 are key regulatory components in the immunosuppressive transforming growth factor- (TGF-) β signaling pathway, which is defective in inflammatory bowel disease (IBD). SMAD4 may play an important role in the pathogenesis of IBD as indicated in experimental models of colitis. Aims. To examine the ileal expression levels of SMAD4 and to correlate these with CD disease activity. Methods. The material comprised 29 CD patients (13 with active disease, 16 in remission) and 9 asymptomatic patients referred for ileocolonoscopy as part of an adenoma surveillance program serving as controls. Patients were examined with ileocolonoscopy. Corresponding ileal biopsies were obtained for histological analysis and assessment of SMAD4 and SMAD7 protein expression by immunohistochemistry (IHC). Results. The protein expression of SMAD4 was significantly downregulated in ileal tissue sections from CD patients as compared to healthy controls (p<0.001). Further, luminal SMAD4 expression was inversely correlated with endoscopic (rs=−0.315; p=0.05) and histopathological activity (rs=−0.40; p=0.013). Conclusions. The SMAD4 epithelial protein level was markedly downregulated in CD patients and inversely correlated with disease activity. This may contribute to defective mucosal TGF-β signaling in active IBD.